Peran Bimbingan Konseling Terhadap Perkembangan Emosional Siswa - Sheila Natasya Murni; Wahdaniati Bancin; Fitri Nur Azizah; Arlina Arlina (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the role of guidance counseling on students' emotional development. This type of research is phenomenological research with qualitative research methods. The instrument used was an interview. The results of this research show that some students experience difficulties in communicating and managing emotions. So counseling helps students understand and manage their own emotions so that they can be more effective in dealing with challenging situations.